Immune response of DNA vaccinated-gilthead seabream (Sparus aurata) against LCDV-Sa infection: relevance of the inflammatory process - Leiva Rebollo, Rocío; Gémez Mata, Juan; Castro-López, María Dolores; Borrego García, Juan José; Labella Vera, Alejandro Manuel (Frontiers, 2023)
Lymphocystis disease is one of the main viral pathologies affecting cultured gilthead seabream (Sparus aurata) in the Mediterranean region. Recently, we have developed a DNA vaccine based on the major capsid protein (MCP) of the Lymphocystis disease virus 3 (LCDV-Sa). The immune response triggered by either LCDV-Sa infection or vaccination have been previously studied and seem to be highly related to the modulation of the inflammatory and the IFN response. However, a comprehensive evaluation of immune-related gene expression in vaccinated fish after viral infection to identify immunogenes involved in vaccineinduced protection have not been carried out to date. The present study aimed to fulfill this objective by analyzing samples of head-kidney, spleen, intestine, and caudal fin from fish using an OpenArray® platform containing targets related to the immune response of gilthead seabream. The results obtained showed an increase of deregulated genes in the hematopoietic organs between vaccinated and non-vaccinated fish. However, in the intestine and fin, the results showed the opposite trend. The global effect of fish vaccination was a significant decrease (p<0.05) of viral replication in groups of fish previously vaccinated, and the expression of the following immune genes related to viral recognition (tlr9), humoral and cellular response (rag1 and cd48), inflammation (csf1r, elam, il1b, and il6), antiviral response (isg15, mx1, mx2, mx3), cell-mediated cytotoxicity (nccrp1), and apoptosis (prf1). The exclusive modulation of the immune response provoked by the vaccination seems to control the progression of the infection in the experimentally challenged gilthead seabream.
Keywords: Cultivos - Virus; DEGs; OpenArray®; Gilthead seabream; DNA-vaccine; Inflammation; Innate immune response; LCDV-Sa